-25(-8x+6)=-750

Simple and best practice solution for -25(-8x+6)=-750 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -25(-8x+6)=-750 equation:


Simplifying
-25(-8x + 6) = -750

Reorder the terms:
-25(6 + -8x) = -750
(6 * -25 + -8x * -25) = -750
(-150 + 200x) = -750

Solving
-150 + 200x = -750

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '150' to each side of the equation.
-150 + 150 + 200x = -750 + 150

Combine like terms: -150 + 150 = 0
0 + 200x = -750 + 150
200x = -750 + 150

Combine like terms: -750 + 150 = -600
200x = -600

Divide each side by '200'.
x = -3

Simplifying
x = -3

See similar equations:

| 2x+12=57-3x | | 4x+10+3x+5+5x-25=180 | | 4x^2+1=6x | | 8x-9=8(x+2) | | 4x+10+3x+5+5x-25=90 | | 2x+8=43-3x | | 6x+8y=226 | | 9(3)+3y=54 | | 8x-10=3x-10 | | 9+11x=99+x | | 9x+3(0)=54 | | 6X-3=2x-6 | | 9(0)+3y=54 | | c^2=8c | | 5x+3x+(2x+5)=180 | | 8m-26=-50+4m | | 8(d-5)+(4d+7)= | | 9x+6-3x=-8+4x | | -1(5a+6)=2(3a+8) | | 8m-2b=-50+4m | | 8x+(2x+5)=90 | | 7x+12= | | 5x-1=13x-57 | | 5x-7(-10)=35 | | 7b-16=-18+9b | | 8z-9=9z-3 | | -4(5n-6)+3n= | | 5x-7(0)=35 | | b+(b-4)=(b+5)-(b+1) | | 5x+3x=(2x+5) | | -7t+3t= | | -2(3x-4)=2x |

Equations solver categories